Social change and everyday life in Ireland, 1850-1922 - Clear, Caitríona, 1960- (Manchester University Press ; Distributed exclusively in the USA by Palgrave, 2007)
Men and women who were born, grew up and died in Ireland between 1850 and 1922 made decisions based on the knowledge and resources they had at the time. This social history of Ireland for the years 1850-1922 to appear since 1981, tries to understand that knowledge and to discuss the resources, for men and women at all social levels on the island.